5th JBF Symposium: 'Bridging for a Global Harmonization'. (October 2014) - Kobayashi, Nobuhiro
Tower Hall Funabori, Tokyo, Japan, 6–7 March 2014 At the 5th Japan Bioanalysis Forum symposium, distinguished bioanalytical scientists from government and industry commentated on the bioanalytical method validation guidelines/guidance issued by their own regions, including the draft bioanalytical method validation guideline for ligand binding assay by the Japanese Ministry of Health, Labour and Welfare, which was finalized in April 2014. Additionally, the Japan Bioanalysis Forum Discussion Group, in which daily bioanalytical issues/interests were scientifically discussed, picked up five topics, and more than 200 conference attendees openly exchanged their views on a wide range of bioanalytical issues with discussion group members. This manuscript provides an overview of the highlights out of the symposium.